Linkages between Agriculture and Food Industry, and Food Processing by Farmers in Korea - 국승용 (한국농촌경제연구원, 2012)
The food industry’s development is relatively closely linked with the development of upstream industries such as farming that supply raw ingredients. As a result of this study, it is proven that agriculture and the food industry are closely connected in the food system structure and input structure of agricultural products. Using an effect analysis, we confirmed that the food industry has the characteristic of having bigger backward linkage effect than forward linkage effect. The farmers’ attitude toward food processing varies from product to product. In the case of fresh agricultural products that are difficult to store long term, the ratio of farmers making use of processing to get rid of low-quality off-grade agricultural products was high. However, in the case of bean, which is easy to store long term, it was shown that farmers prefer processing since they can sell it as a raw ingredient at a higher unit price. It is necessary to prepare measures that would allow stable procurement of raw ingredients by expanding the transaction volume through farmers’ alliance. Moreover, it is necessary to build a foundation for stable production of processed foods by developing various processed food products using fresh products and by opening up new markets.
Keywords: food system; agriculture; vertical coordination; index of power of dispersion; index of sensitivity of dispersion; food system; agriculture; vertical coordination; index of power of dispersion; index of sensitivity of dispersion